A review of tectonic models for the rifted margin of Afar: Implications for continental break-up and passive margin formation. (April 2020) - Zwaan, Frank; Corti, Giacomo; Keir, Derek; Sani, Federico
Abstract: The Afar region represents a unique opportunity for the study of ongoing rift development and the various phases of continental break-up. In this work we discuss the geological and geomorphological characteristics of the Western Afar Margin (WAM) and the various scenarios proposed for its evolution. A drastic decline in topography and crustal thickness from the Ethiopian Plateau into the Afar Depression, as well as a series of marginal grabens and a general presence of antithetic faulting characterize the WAM. Present-day extension is mostly accommodated at the rift axis in Afar, yet the margin is still undergoing significant deformation. Models for the evolution of the WAM involve either isostatic loading effects due to erosion, rifting-induced block rollover, large-scale detachment fault development or crustal flexure due to lithospheric stretching or magmatic loading. This wide variation of potential mechanisms for WAM development may reflect a general structural variation along the margin and in Afar, involving different stages of rift formation and possibly indicating two distinct pathways leading to continental break-up. In order to better understand the rifting mechanisms and to fully exploit the research potential of the region, further assessment of the WAM and its relation to Afar will be necessary. The findings of such future work, combined with data from rifts and passive margins from around the globe will be of great importance to assess the processes involved in continental breakup and to better constrain the sequence of events leading from initial rifting to break-up and oceanic spreading. Highlights: We compare tectonic models for the evolution of the Western Afar Margin (WAM). Antithetic faulting and marginal grabens characterize this poorly studied margin. Seismic activity reveals ongoing deformation; the WAM is not a passive margin yet. Regional data suggest magmatism controls the main pathways to continental breakup. We propose strategies to improve our knowledge of the WAM and break-up in general.